2013
DOI: 10.6061/clinics/2013(07)09
|View full text |Cite
|
Sign up to set email alerts
|

Serum albumin level as a risk factor for mortality in burn patients

Abstract: OBJECTIVE:Hypoalbuminemia is a common clinical deficiency in burn patients and is associated with complications related to increased extravascular fluid, including edema, abnormal healing, and susceptibility to sepsis. Some prognostic scales do not include biochemical parameters, whereas others consider them together with comorbidities. The purpose of this study was to determine whether serum albumin can predict mortality in burn patients.METHODS:We studied burn patients ≥16 years of age who had complete clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 36 publications
(23 reference statements)
4
65
0
1
Order By: Relevance
“…Moreover, note that those at the highest risk of death with albumin levels of less than 20 g/L [20] were 6 (7.3%) and 15 (18.3%) initially and in the post-resuscitation phases, respectively in this study. It follows that a significant number of our patients may have been at risk of passing away even though none actually expired in the burn shock phase.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, note that those at the highest risk of death with albumin levels of less than 20 g/L [20] were 6 (7.3%) and 15 (18.3%) initially and in the post-resuscitation phases, respectively in this study. It follows that a significant number of our patients may have been at risk of passing away even though none actually expired in the burn shock phase.…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, hypertonic crystalloid saline has been associated with renal failure and death in one observational study and seems to offer no added benefit to isotonic solutions [18] [19]. However, there is a resurgence in interest in albumin and a relatively recent study [20] having shown that albumin levels of less than about 2 g/dl (20 g/L) emerged with the highest sensitivity and specificity for mortality. …”
Section: Introductionmentioning
confidence: 99%
“…Previous authors have [24][25][26]. Low serum albumin levels have also been used as predictors of poor outcome in other diseases as well [27][28][29]. Hypoalbuminaemia is an indicator of protein energy depletion and a marker of poor nutritional status; furthermore, it increases the risk of postoperative complications including poor wound healing, wound infections, pneumonia, and sepsis.…”
Section: Biochemical Parametersmentioning
confidence: 97%
“…Aguayo-Becerra et al [18] reported that burn patients with albumin levels <2 g/dL at admission had a mortality risk of >80%, with 84% sensitivity and 83% specificity. Maldonado et al [19] investigated the role of some biochemical variables including albumin and calcium levels in the prediction of mortality in 143 patients with major burns hospitalized in the ICU but reported that in a multi-variate analysis, only age, the total body surface area burned, the pH value, and the magnesium levels were independently associated with mortality.…”
Section: Discussionmentioning
confidence: 99%